Sirt1 in cerebral ischemia - Kevin B Koronowski; Miguel A Perez-Pinzon (Brain Circulation, 2015)
Cerebral ischemia is among the leading causes of death worldwide. It is characterized by a lack of blood flow to the brain that results in cell death and damage, ultimately causing motor, sensory, and cognitive impairments. Today, clinical treatment of cerebral ischemia, mostly stroke and cardiac arrest, is limited and new neuroprotective therapies are desperately needed. The Sirtuin family of oxidized nicotinamide adenine dinucleotide (NAD +)-dependent deacylases has been shown to govern several processes within the central nervous system as well as to possess neuroprotective properties in a variety of pathological conditions such as Alzheimer′s Disease, Parkinson′s Disease, and Huntington′s Disease, among others. Recently, Sirt1 in particular has been identified as a mediator of cerebral ischemia, with potential as a possible therapeutic target. To gather studies relevant to this topic, we used PubMed and previous reviews to locate, select, and resynthesize the lines of evidence presented here. In this review, we will first describe some functions of Sirt1 in the brain, mainly neurodevelopment, learning and memory, and metabolic regulation. Second, we will discuss the experimental evidence that has implicated Sirt1 as a key protein in the regulation of cerebral ischemia as well as a potential target for the induction of ischemic tolerance.